Development of Students Social and Value Orientations Towards Training State and Municipal Management - Rezer, Tatiana; Nevsky, Grigory (KnE Social Sciences, 2021)
The purpose of this study is to analyze scientific research in the field of training civil servants, as well as to conduct a study on the development of socially significant values of students studying in the direction “State and Municipal Management”. The technology for the development of social and professional value orientations in students (by Rezer T. M., Khokholush M. S.) and the method by M. Rokeach are used to determine the students’ social and value orientations development level and subjects of their personal needs that determine the life guidelines of the future civil servant. The main research results have shown that in recent years various subject areas for the training of public servants, such as the challenges and quality of education; pedagogical conditions and behaviors; professional potential development, traditions and innovations in professional activity have been actively studied. The study has shown that the ranks from 1 to 5 are occupied by the terminal values: “Health”, “Happy family life”, “Love”, “Financially secure life”, “Interesting work”. In the group of the instrumental values, at the ranks from 1 to 5 there were the values: “Good manners”, “Responsibility”, “Honesty”, “High demands”, “Intransigence to shortcomings in oneself and others”. Keywords: students’ social and value orientations, development, state and municipal management, state and municipal employees’ training